Becoming a Poet: A Narrative Analysis in Predicting Schwartz's Values in the Artist Acep Zamzam Noor - Diya Bulan Farida; Mirra Noor Milla (PT Mattawang Mediatama Solution, 2023)
Acep Zamzam Noor, a renowned artist from West Java known for his works in painting and literature, is now fully dedicated to advancing his work in the world of literature. Despite a journey filled with challenges, his spirit has inspired the artistic community and organizations, driving positive change for the younger generation in supporting art and culture. This research employs a qualitative method with narrative analysis to reveal values that reflect the personality of